Implication of design process and economic consideration on jewellery product / HZ Hashim ... [et al.] - Hashim, HZ; KAA, Rahman; Alli, H; Effendi, RAAR (2019)
As eyes are the windows to a person’s soul, design reveals intimate expressions of one’s desire. In an evolving economy, the role of jewellery design process focuses on what is affordable in the jewellery design as an end product should satisfy consumers’ affordability in acquiring a piece of jewellery. As overall living costs escalate, sustainability and continuity of one’s livelihood is a serious consideration. With reference to the jewellery industry where design is the competitive edge, many studies have been conducted on types of jewellery. Pertaining to previous studies that were conducted in fragments and focuses only on a few stages of the jewellery design process; pre-production should ensure economics of production to be adhered by design to ascertain owner's value add benefit. Design process of an adornment should adhere to the acquiring capability of consumers’ reality and translate into tangible economical value to each customer. Gold, a thing of beauty and a strong form of collateral is proven to be a favourable contingency plan in many households. This research shall provide insights into the importance of the role of jewellery design process developing economic climate as developed on the basis of interview results from the retail jewellery industry in Malaysia.